Successful Diagnoses and Remarkable Metabolic Disorders in Patients With Solitary Hypothalamic Mass: A Case Series Report - Xiang, Boni; Sun, Quanya; He, Min; Wu, Wei; Lu, Bin; Zhang, Shuo; Zhang, Zhaoyun; Yang, Yehong; Li, Yiming; Wu, Yue; Yao, Zhenwei; Cheng, Haixia; et al. (Frontiers in Endocrinology, 2021)
Background: Solitary intracranial hypothalamic mass occurs rarely. The etiological diagnosis of solitary hypothalamus lesion is challenging and often unachievable. Although previous studies indicated that lesions affecting the hypothalamus often cause significant metabolic disorders, few reports about the metabolic disturbances of patients with solitary hypothalamic mass have been reported. Method: Twenty-five patients with solitary hypothalamus lesions who had been evaluated and treated in Huashan Hospital from January 2010 to December 2020 were retrospectively enrolled. The clinical manifestations, radiological features, endocrine and metabolic disorders, and pathology were analyzed. Results: The male to female ratio was 5/20. The median age of onset was 22 (19, 35) years old. The most common initial symptom was polydipsia/polyuria (19/25, 76.0%) and amenorrhea (9/20, 45.0%). A high prevalence of hypopituitarism of different axes was found, with almost all no less than 80%. Central hypogonadism (21/22, 95.5%) and central diabetes insipidus (19/21, 90.5%) were the top two pituitary dysfunctions. Conclusive diagnoses were achieved by intracranial surgical biopsy/resection or stereotactic biopsy in 16 cases and by examining extracranial lesions in 3 cases. The pathological results were various, and the most common diagnoses were Langerhans cell histiocytosis (7/19) and hypothalamitis (5/19). The mean timespan from onset to diagnosis in the 19 cases was 34±26 months. Metabolic evaluations revealed remarkable metabolic disorders, including hyperlipidemia (13/16, 81.3%), hyperglycemia (10/16, 62.5%), hyperuricemia (12/20, 60%), overweight/obesity (13/20, 65.0%), and hepatic adipose infiltration (10/13, 76.6%). Conclusion: Either surgical or stereotactic biopsy will be a reliable and relatively safe procedure to help to confirm the pathological diagnosis of solitary hypothalamic mass. Metabolic disorders were severe in patients with solitary hypothalamic mass. The management of such cases should cover both the treatment of the primary disease, as well as the endocrine and metabolic disorders